Analisis Pengaruh Kemajuan Sustainable Development Goals (SDGs) terhadap Pembangunan Pendidikan Karakter: Suatu Kajian dalam Konteks Perubahan Sosial Global - Marlinda, Sherly (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Education is a common thing and is a basic right for every human being living on earth. Proper education can lead humans to the gates of glory and will promise progress for the nation and state. This research aims to conduct a study of SDGs progress towards character education development. The method used is descriptive analysis, namely by searching and collecting reference sources from previously published articles/journals for study. The research results show that the presence of SDGs programs that are in line with Indonesia's educational goals has a good influence on improving character education in Indonesia. Especially at a time when society is increasingly dependent on the convenience of technology and the lack of a proper education system throughout the country.